PENINGKATAN MODAL SOSIAL MASYARAKAT DALAM PENYELESAIAN KONFLIK MELALUI MEDIASI: KASUS KHDTK MENGKENDEK, KABUPATEN TANA TORAJA - Abd. Kadir Wakka (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2018)
Conflict of interest between management of Special Purpose Forest Area (KHDTK) with community surrounding the forest has caused KHDTK functions are not optimal. The approach through law enforcement has not been able to resolve the conflicts, so that mediation approach has been taken. This study aims to determine the impact of mediation approach on the community social capital around KHDTK Mengkendek. Data were collected through participatory action research (PAR) approach. Qualitative descriptive technique was used to analyse the data. The results showed that mediation approach in resolving conflicts in KHDTK Mengkendek had an impact on the community social capital around KHDTK. Level of trust of the surrounding community toward KHDTK Mengkendek manager is getting stronger. In addition, number of norms have been compiled and set forth in the text draft of forestry partnership agreement. A concept of Mengkendek KHDTK management network has started to be designed. The improvement of social capital of the community around KHDTK Mengkendek is expected to mitigate the conflict that occurs so that the function of KHDTK for research and development can be optimized.